THE ROLE OF SUSTAINABILITY IN REVERSE LOGISTICS FOR RETURNS AND RECYCLING - Ali, Ahmed Hussein; Zalavadia, Siddharth; Barakat, Mahmoud Ramadan; Eid, Ahmed (Archives of Business Research, 2018)
The purpose of this research is to measure the impact of reverse logistics performance indicators namely; cost, recycling efficiency, time, quality and waste on sustainability performances (Economic, Environmental and Social) in in Fast Moving Consumer Goods (FMCG) industries. To reach this aim primary data was collected through 116 online survey, to test the hypothesized relationship between reverse logistics performance indicators and sustainability. For the purpose of this research the questionnaire was distributed to key personnel in reverse logistics processes working at FMCG industry. The results concluded that reverse logistics performance indicators have a significant positive impact on environmental performance, except for waste. In addition, economic performance is positively influenced by only recycling efficiency and quality. Finally, it was found that only recycling efficiency can positively influence social performance. These findings includes implications for the development of implementing sustainability in revers logistics, in addition it provide companies with the guidance to apply sustainability in revers logistics. Finally, this paper adds value to the industries by measuring the role of sustainability in revers logistics.